Play and playfulness for health and wellbeing: A panacea for mitigating the impact of coronavirus (COVID 19). Issue 1 (2021) - Tonkin, Alison; Whitaker, Julia
Abstract: In the early part of 2020, the coronavirus pandemic challenged human sociability as social distancing measures were introduced in an attempt to break 'the chain of infection'. A central component of human sociability is our innate ability to play and be playful, individually or together, for our own enjoyment or for the benefits of others. This article explores the adaptive benefits of play and playfulness for health and wellbeing, at a time when community assets such as family, friendships, neighbours and community groups are physically inaccessible as we abide by the UK government requirement to Stay at Home, Protect the NHS, Save Lives. Using the Five Ways to Wellbeing, numerous examples showing how people have been able to 'connect, be active, take notice, keep learning and give' during the coronavirus crisis, exemplifies the transformative power of play and playfulness and the best of human endeavour.